Peran Orang Tua terhadap Keterampilan Membaca Permulaan Siswa Kelas II SDN Lerep 04 Ungaran Barat Kabupaten Semarang - Lestari, Puput; Wijayanti, Atrianing Yessi; Puspitasari, Nimas (Faculty of Teacher Training and Education of Undaris, 2026)
Beginning reading is a fundamental skill that must be mastered by elementary school students,particularly in the early grades, as it serves as the foundation for further learning. Students with lowbeginning reading ability may experience difficulties in understanding instructional materials and achievingacademic success. This study aimed to describe the role of parents in supporting the beginning reading skillsof second-grade students at SDN Lerep 04, West Ungaran, Semarang Regency. This study employed aqualitative descriptive design involving one second-grade teacher, six parents, and six second-gradestudents. Data were collected through interviews and documentation and were validated using sourcetriangulation. The data were analyzed through data reduction, data display, and conclusion drawing. Thefindings revealed that parents played important roles as educators, facilitators, companions, and motivators.They supported children by introducing letters, guiding them in reading syllables and simple words,providing learning materials and facilities, accompanying them during reading activities at home, andencouraging them through praise, advice, and rewards. However, several obstacles were identified,including gadget use, limited parental time, children’s changing moods, and the influence of the playenvironment. The study concludes that the optimization of parental roles significantly contributes to thedevelopment of children’s beginning reading skills. Therefore, strong collaboration between schools andfamilies is essential to foster literacy from an early age.Keywords: parental role, beginning reading, reading skills, elementary school students